Chordomas at High Prevalence in the Captive Population of the Endangered Perdido Key Beach Mouse (Peromyscus polionotus trissyllepsis). (January 2016) - Taylor, K. R.; Garner, M. M.; Russell, K.; Epperson, E. D.; Grodi, H. A.; Roff, S. R.; Dumonceaux, G. A.; Struthers, J. D.; Dark, M. J.; Abbott, J. R.
The Perdido Key beach mouse ( Peromyscus polionotus trissyllepsis ) is a critically endangered subspecies of the oldfield mouse. The captive population, currently maintained by 3 Florida zoos, is entirely derived from just 3 wild-caught ancestor mice. Necropsy and histopathology revealed chordoma of the vertebral column in 38 of 88 (43%) mice. The tumors were locally expansile and invasive masses of large physaliferous (vacuolated) cells with small, round, hyperchromatic nuclei, similar to the "classic" form of chordomas described in humans. Primary tumors rarely contained small amounts of bone and cartilaginous matrix, characteristic of the "chondroid" form. Neoplastic cells contained abundant granules positive by the periodic acid–Schiff reaction. Brachyury and cytokeratin AE1/AE3 were detected in neoplastic cells by immunohistochemistry, but uncoupling protein 1 was not identified. Primary tumors occurred along the entire vertebral column—cervical, 5 of 38 (13%); thoracic, 16 (42%); lumbar, 13 (34%); and sacral, 10 (26%)—and 10 (26%) mice had multiple primary masses. Metastases to the lungs were noted in 13 of the 38 (34%) mice. Mice diagnosed with chordomas postmortem ranged from 424 to 2170 days old, with a mean of 1399 days. The prevalence of chordoma was not significantly different between males ( n = 23 of 50; 46%) and females ( n = 15 of 38; 39%).